Defining Community of Practice in the Context of Activity Theory - Uden, Lorna; S.M.F.D, Syed Mustapha (2011)
Knowledge is significant part of the assets of any organisation. The utilization and continuous crea-tion of knowledge are the most important managerial challenges organisations face today. While the technol-ogy for collecting, storing, and accessing information continues to grow exponentially, the ability to effec-tively and efficiently use this information to enhance job performance, as well as deliver quality products and services remains elusive. The challenge is to foster human interaction and Knowledge Sharing (KS) by creating an environment that truly values KS. The sharing of knowledge (not just information) among the members of an enterprise created the communities of practice (CoPs), which aimed at learning from one another to achieve a common goal, e.g. that of a group of people with common interests. We believe that creating the right environment to foster sharing and collaboration is a critical component of knowledge man-agement. The environment should connect people, processes, and information. However, the design of an effective knowledge sharing environment is not trivial. Technical knowledge is inadequate. It also requires social and cultural knowledge. Based on our experience with communities of practice, we have created a knowledge sharing community model using activity theory to allow users to co create value in sharing knowledge. This paper describes the design of a knowledge sharing environment that incorporates technical, social and cultural aspects of CoP.